2019
DOI: 10.1111/pedi.12825
|View full text |Cite
|
Sign up to set email alerts
|

Serum catestatin concentrations are decreased in obese children and adolescents

Abstract: Background: Catestatin is a chromogranin A-derived peptide with a wide spectrum of biological activities, such as inhibiting catecholamine release, decreasing blood pressure, stimulating histamine release, reducing beta-adrenergic stimulation, and regulating oxidative stress.Objectives: The aims of our study were to determine serum catestatin concentrations in obese children and adolescents in regard to presence or absence of metabolic syndrome (MS) and to evaluate the possible relations between catestatin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 55 publications
2
31
0
3
Order By: Relevance
“…Of note, catestatin suppressed hepatic glucose production and was associated with improved insulin sensitivity in mice with diet-induced obesity [45], while it also induced glucose uptake and GLUT4 trafficking in adult rat cardiomyocytes, thus, likely improving cardiac energetics [46]. One study performed among obese children and adolescents found that catestatin negatively correlated with the homeostatic model assessment of insulin resistance (HOMA-IR) and its levels were significantly reduced in obese subjects, compared to the control group [47]. CST also improved peripheral leptin sensitivity and promoted lipolysis and fatty acid oxidation in a preclinical model [48], thus, confirming its antiobesic effect [49].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, catestatin suppressed hepatic glucose production and was associated with improved insulin sensitivity in mice with diet-induced obesity [45], while it also induced glucose uptake and GLUT4 trafficking in adult rat cardiomyocytes, thus, likely improving cardiac energetics [46]. One study performed among obese children and adolescents found that catestatin negatively correlated with the homeostatic model assessment of insulin resistance (HOMA-IR) and its levels were significantly reduced in obese subjects, compared to the control group [47]. CST also improved peripheral leptin sensitivity and promoted lipolysis and fatty acid oxidation in a preclinical model [48], thus, confirming its antiobesic effect [49].…”
Section: Discussionmentioning
confidence: 99%
“…Obese children and adolescents have a significantly lower serum CST levels than those in healthy controls. In a cohort of obese children, those with any symptoms of metabolic syndrome or increased cardiovascular risk had the lowest serum CST levels[ 45 ].…”
Section: Granin Peptides In Glucose Homeostasismentioning
confidence: 99%
“…There are no significant correlations between serum CgA and CgB levels [ 47 ]. Serum catestatin levels are decreased in patients with metabolic syndrome compared with patients in the control category [ 51 ].…”
Section: Biomarker For Diabetes Metabolic Syndrome and Cardiovascular Diseasementioning
confidence: 99%